UMPSA celebrates media practitioners and strategic partners in Iftar Ceremony - Naqiah, Puaad (UMPSA, 2025)
KUANTAN, 19 March 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) today held a Collaboration Programme and Iftar Ceremony with media practitioners and strategic partners at Hotel Mega View, Kuantan, as an initiative to strengthen good relations and appreciation for the role of the media in disseminating information and supporting the university’s development.